2020
DOI: 10.15252/msb.20209888
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals insights into infant immunological and febrile responses to group B meningococcal vaccine

Abstract: Neisseria meningitidis is a major cause of meningitis and septicaemia. A MenB vaccine (4CMenB) was licensed by the European Medicines Agency in January 2013. Here we describe the blood transcriptome and proteome following infant immunisations with or without concomitant 4CMenB, to gain insight into the molecular mechanisms underlying post-vaccination reactogenicity and immunogenicity. Infants were randomised to receive control immunisations (PCV13 and DTaP-IPV-Hib) with or without 4CMenB at 2 and 4 months of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Our results clearly demonstrate a rise in inflammatory markers post vaccination, as has previously been reported post immunisation even in children not requiring medical attention. 8 We observed that neither WCC or neutrophils are helpful in predicting IBI in this context. This is consistent with known limitations in their use outside the post immunisation period.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our results clearly demonstrate a rise in inflammatory markers post vaccination, as has previously been reported post immunisation even in children not requiring medical attention. 8 We observed that neither WCC or neutrophils are helpful in predicting IBI in this context. This is consistent with known limitations in their use outside the post immunisation period.…”
Section: Discussionmentioning
confidence: 62%
“…2 Additionally, the immunological response to vaccination is known to cause a transient rise in inflammatory markers in infants with and without AEFI. In particular CRP, granulocyte colony stimulating factor, interleukin (IL)-1RA and IL-6 have been shown to rise 24 hours post vaccination, with corresponding neutrophil activation, 8 further complicating differentiating AEFI from IBI.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Systems biology approaches have been used to evaluate immune responses to vaccines, e.g. yellow fever (15)(16)(17), meningococcus (18,19), pneumococcal (18,20) and influenza (21)(22)(23) and have been powerful tools for elucidating immunological correlates of vaccine responses. In the context of seasonal influenza vaccination, gene sets related to immunoglobulins, complement proteins, and cellular proliferation are strongly enriched in vaccine responders compared to non-responders 7 days post-vaccination (22).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has also been extended into mice for the exploratory analysis of different vaccine platforms and components through whole blood transcriptomics, for example for the acellular pertussis vaccine and pertussis outer membrane vesicles (OMVs) [ 25 , 26 ], and a variety of novel vaccine adjuvants [ 27 ]. We previously applied comparative transcriptomics to identify molecular determinants of vaccine-induced reactogenicity within the first 24 h post-immunisation in mice and infants [ 28 , 29 ]. There is a paucity of data related to the transcriptional responses induced by viral vector vaccines.…”
Section: Introductionmentioning
confidence: 99%